Pengaruh Media Permainan Ular Tangga terhadap Hasil Belajar Kosakata Bahasa Arab Siswa Kelas III E SDIT Raudhatul Jannah Cilegon - Muhlisoh, Khulasatul; Uyuni, Yuyun Rohmatul (Perhimpunan Sarjana Ekonomi dan Bisnis, 2025)
Vocabulary is a fundamental element in language learning. With a good command of vocabulary, a person can compose perfect sentences to interact between individuals. Vocabulary in the world of elementary school education is a lesson that must be obtained by students, especially in Islamic-based school institutions. Facts at school show the low mastery of Arabic vocabulary caused by several problems, including the use of conventional teaching methods, media, and strategies so that learning is not considered fresh and feels dull, pronouncing Arabic among elementary school students is also a problem. Therefore, the author applies a fun media in teaching Arabic vocabulary, namely through the snakes and ladders game with a pre-experimental one group design research method to determine whether or not there is an effect after applying the game media in one class without a control class. This game uses a numbered board with pictures of snakes and ladders and is equipped with dice to determine the forward or backward movements that players must make to reach the finish line through various challenges in the question cards. Based on the results of the study, the Arabic vocabulary value of students in class III E SDIT Raudhatul Jannah has increased after applying snakes and ladders game media. The increase is evidence of the effect of the application of snakes and ladders game on the percentage of value completeness. Before using the snakes and ladders game was 62% with an average of 73. As for after using the snakes and ladders game, the percentage of students' score completeness increased to 94% with an average of 95.